2023
DOI: 10.1038/s41525-023-00375-8
|View full text |Cite
|
Sign up to set email alerts
|

Population-based prevalence and mutational landscape of von Willebrand disease using large-scale genetic databases

Omid Seidizadeh,
Andrea Cairo,
Luciano Baronciani
et al.

Abstract: Von Willebrand disease (VWD) is a common bleeding disorder caused by mutations in the von Willebrand factor gene (VWF). The true global prevalence of VWD has not been accurately established. We estimated the worldwide and within-population prevalence of inherited VWD by analyzing exome and genome data of 141,456 individuals gathered by the genome Aggregation Database (gnomAD). We also extended our data deepening by mining the main databases containing VWF variants i.e., the Leiden Open Variation Database (LOVD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The variant has an overall minor allele frequency of 0.003442 in the Genome Aggregation Database. We previously showed that it is among the most recurrent VWD-associated variants in the Non-Finnish European population [ 9 ]. In order to determine the role of this frequently reported VWF variant, it is necessary to gather data from multiple centers on large populations.…”
mentioning
confidence: 99%
“…The variant has an overall minor allele frequency of 0.003442 in the Genome Aggregation Database. We previously showed that it is among the most recurrent VWD-associated variants in the Non-Finnish European population [ 9 ]. In order to determine the role of this frequently reported VWF variant, it is necessary to gather data from multiple centers on large populations.…”
mentioning
confidence: 99%